WORK CULTURE AND JOB SATISFACTION ON PERFORMANCE WITH MOTIVATION AS INTERVENING VARIABLE - Desratri Nisa Romadhani; Kusuma Chandra Kirana; E. Didik Subiyanto (Jurnal Riset Bisnis dan Manajemen, 2022)
This study aims to determine the effect of work culture and job satisfaction on employee performance with work motivation as an intervening variable in Badan Pertanahan Nasional (BPN) Kulon Progo. This study uses the Accidental Sampling method with a research sample of 61 employees. Based on this research the work culture had no effect on work motivation meanwhile job satisfaction had positive effect on work motivation. Work motivation and work culture had a significant and positive on performance. Job satisfaction had no significant effect on performance. Work motivation did not have an impact to work culture on employee performance but it had a significant impact to job satisfaction on employee performance.